Three cases of imported eyeworm infection in dogs: a new threat for the United Kingdom. (30th September 2017) - Graham‐Brown, John; Gilmore, Paul; Colella, Vito; Moss, Lyndsay; Dixon, Chris; Andrews, Martin; Arbeid, Peter; Barber, Jackie; Timofte, Dorina; McGarry, John; Otranto, Domenico; Williams, Diana
Abstract : In July 2016 we described the first known case of canine ocular thelaziosis in the UK in a dog recently imported from Romania. Here we confirm our initial diagnosis using PCR followed by sequence analysis, and we report a further two clinical cases in dogs with recent history of travel to Italy and France. In view of the presence in the UK of the vector for Thelazia callipaeda, namely Phortica spp, we discuss the significance of these three cases in the context of the UK government's pet travel scheme, disease control and both animal and public health in the UK.